Speciation analysis of Sn(II) and Sn(IV) using baker's yeast and inductively coupled plasma optical emission spectrometry - Caldorin, Rogerio; Menegario, Amauri A. (Springer, 2007)
The use of Saccharomyces cerevisiae as a substrate to selectively retain Sn(II) and Sn(IV) has been investigated. Several factors affecting the retention of the analytes by yeast, such as pH, amount of biomass, temperature and time of contact were evaluated. Based on this study, a method for determination of Sn(II) and Sn(IV) combining inductively coupled plasma optical emission spectrometry (ICP OES) and solid phase extraction using Saccharomyces cerevisiae is proposed. The procedure consists of the selective retention of Sn(IV) by yeast at pH = 2.0 while Sn(II) remains in solution. Determination of tin in the solid phase was easily carried out by submitting a slurry of the yeast (0.5 g/40 mL) directly to ICP OES. The precision of the extraction procedure was characterized by an RSD lower than 4%. The detection limits of tin (3 sigma) in the solid phase and the liquid phase were 1.1 and 0.7 mu g L-1, respectively. The proposed approach was evaluated for determination of Sn(II) and Sn(IV) in spiked river water and real samples of industrial waste water (untreated and treated). For all samples, recoveries of spiked Sn(II) and Sn(IV) were between 85 and 112%.
Keywords: tin; Sn(IV); Sn(II); Saccharomyces cerevisiae; ICPOES; waste water